South Polar chart / compiled from the latest information in the Hydrographic Department, 1956 (Great Britain. Hydrographic Office, 1956)
New editions 30th Nov. 1956 Depths shown by bathymetric isolines and soundings.; Includes notes and conversion tables.; "Enamel 1949."; "Crown copyright reserved."; "341.56" -- upper right margin.; "Z/en 1956" -- lower right margin. Color;